Allergic Lung Inflammation Aggravates Angiotensin II–Induced Abdominal Aortic Aneurysms in Mice. Issue 1 (January 2016) - Liu, Cong-Lin; Wang, Yi; Liao, Mengyang; Wemmelund, Holger; Ren, Jingyuan; Fernandes, Cleverson; Zhou, Yi; Sukhova, Galina K.; Lindholt, Jes S.; Johnsen, Søren P.; Zhang, Jin-Ying; Cheng, Xiang; et al.
Abstract : Objective—: Asthma and abdominal aortic aneurysms (AAA) both involve inflammation. Patients with asthma have an increased risk of developing AAA or experiencing aortic rupture. This study tests the development of one disease on the progression of the other. Approach and Results—: Ovalbumin sensitization and challenge in mice led to the development of allergic lung inflammation (ALI). Subcutaneous infusion of angiotensin II into mice produced AAA. Simultaneous production of ALI in AAA mice doubled abdominal aortic diameter and increased macrophage and mast cell content, arterial media smooth muscle cell loss, cell proliferation, and angiogenesis in AAA lesions. ALI also increased plasma IgE, reduced plasma interleukin-5, and increased bronchioalveolar total inflammatory cell and eosinophil accumulation. Intraperitoneal administration of an anti-IgE antibody suppressed AAA lesion formation and reduced lesion inflammation, plasma IgE, and bronchioalveolar inflammation. Pre-establishment of ALI also increased AAA lesion size, lesion accumulation of macrophages and mast cells, media smooth muscle cell loss, and plasma IgE, reduced plasma interleukin-5, interleukin-13, and transforming growth factor-β, and increased bronchioalveolar inflammation. Consequent production of ALI also doubled lesion size of pre-established AAA and increased lesion mast cell and T-cell accumulation, media smooth muscle cell loss, lesion cell proliferation and apoptosis, plasma IgE, and bronchioalveolar inflammation. In periaortic CaCl2 injury–induced AAA in mice, production of ALI also increased AAA formation, lesion inflammation, plasma IgE, and bronchioalveolar inflammatory cell accumulation. Conclusions—: This study suggests a pathological link between airway allergic disease and AAA. Production of one disease aggravates the progression of the other. Abstract : Supplemental Digital Content is available in the text.